Da droga ao tóxico: subversão do sujeito no percurso do internamento voluntário - Silva, Fabíola Barbosa Ramos da (2014)
In this research, drug addiction is not synonymous with the dependence on a psychoactive substance, but it is understood as an intense and exclusive relationship in which drug use is also established as a function in mental life. This work aims to analyze landslides in demand for treatment by drug addiction over voluntary admission. Its specific objectives are: to identify the specifics of the drug addict's entry into a treatment institution; investigate the demand of destinations in the accommodation of the route; place the management mode of the institutional place in clinical practice with drug addicts; and articulate the biases of the meeting - between drug addict and institution - with the discourse in vogue in post-modernity. The core of the research is to determine the natural effects of psychoanalytical listening at the institutional level, in favor of subversion of the subject. If to the addicted the drug participate as a dismissal of the subject, to be presented pasted, speaking of himself, only from his use of drugs, the way forward is to offer words. The direction of the treatment, to fetch hear the toxic function of the drug, rather than solely to mind with the use or non-use of a psychoactive substance, can enable the guy who works with his addiction to drugs find room for a significant slide, and that can be placed in work your enjoyment so. Therefore, an engaged institution in the addiction clinic needs to be doubly warned of its function: First, dodge the traffic in line with the institution's postmodern principles, which exalts excess joy and erasing the boundaries ; and second, should know that only to the price of standing in the place of the impossible that it appears as a possible place addressing. The survey was conducted in RAID Institute, an NGO, following the psychoanalytic in its clinical and institutional management and works in prevention and treatment of people of both sexes who voluntarily choose to join it because of problems related to abuse or addiction to alcohol and other drugs. Participated in this research, drug addicts in treatment, fully housed in the institution. Through interviews we tried to go the way that evokes addiction, and reflect the specificities of this Clinic. In conjunction with the cases it is possible to recognize the unique significance and representation of drug use in drug addiction, one of the ways of dealing with the discomfort to invest in toxic as real solution to the subjectivity. Such shifts promoted by the person who is named as abuse drug addict and brings his drug use and volunteer in the hospital, during the course can consent to realize the role that the toxic occupies in his psychic life, and get involved in that. The willingness in treatment is a fundamental ethical component, in that it only from the availability of each subject will be possible to build new itineraries for your own desire.